Influence of Harmonics in Laboratory due to Nonlinear Loads - Risnidar Chan; Ismail Daut; Syafruddin Hasan; Norhaidar Hasim (Institute of Advanced Engineering and Science, 2012)
This research was focused on the customer’s side of the meter which is the effect of harmonics on a laboratory in Electrical System Engineering School at K.Wai Perlis. Harmonic currents in equipments can cause them to experience overheating and increased losses, while harmonic voltage produces magnetic fields rotating at a speed corresponding to the harmonic frequency. This also results in equipments heating, mechanical vibrations and noise, reduced efficiency, reduced life, and voltage stress on insulation of equipment windings. The loads in this research are computers, Compact Fluorescent Lamps CFLs), Air Conditions and printers,which all of the loads are harmonic significant The instrument to measure and monitoring is Fluke 435 Power Quality Analyzer. With the operation of varying nonlinear loads, the injected harmonic current magnitudes and phase angles vary in a random way. This research offers the advantage of providing the utility a wealth of information on the effects of harmonics in their equipments. This will subsequently make them aware of the causes of increased cost and reduced efficiency that may be experienced by using these equipments. This paper describes the investigation cost of harmonic effect as THD, and harmonic energy losses cost.Keywords: harmonics, nonlinear loads, Energy losses cost, THD.DOI: http://dx.doi.org/10.11591/ijpeds.v2i2.142